Foliar application of humic liquid extract from vermicompost improves garlic (Allium sativum L.) production and fruit quality - D. M. Balmori; C. Y. A. Domínguez; C. R. Carreras; S. M. Rebatos; L. B. P. Farías; F. G. Izquierdo; R. L. L. Berbara; Andrés Calderín García (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The beneficial effects of liquid humus applied to plants are well reported in the literature; however, studies of liquid humic application in the production and quality of garlic culture are practically nonexistent. The objective of this work was to evaluate the effects of foliar application of a liquid humic extract from vermicompost (HEVC) that is well characterized by solid-state 13C NMR on garlic production and fruit quality under field conditions. Method After 45 days in the field, garlic plants received foliar applications of HEVC at three different dilutions: 1:40, 1:60 and 1:80 (v:v). Humic substances (HS) in HEVC were characterized by 13C NMR CP/MAS spectroscopy. At 125 days after planting, the plants were collected, and growth and production parameters were determined: quantity of garlic cloves, fresh and dry bulb, diameter of garlic cloves and bulb, as well as parameters of fruit quality including caliber, firmness, acidity, brix, pungency, carbohydrate and protein contents. Results The structure of HS in HEVC is composed mainly of carbohydrates and peptides as well as lignin fragments, explaining the stimulus effects on plant metabolism. The foliar application of HEVC improves the productive, commercial and internal quality parameters of fruits when compared to the control treatment. The HEVC foliar application in 1:40 v:v ratio was the most promising treatment in terms of increases in fruit quality indices, promoting improvements in bulb caliber, numbers of garlic cloves and internal fruit content. Conclusion The foliar application of HEVC benefits garlic production and fruit quality. The use of HEVC can be a sustainable alternative within the small-scale garlic phytotechnology package.